Production of Resistant Starch from Legume Flour by Co-Fermentation and Using Pullulanase and Retrogradation - Wittanalai, Suttida (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2024)
This research aimed to investigate the effect of fermentation and using pullulanase and retrogradation time on resistant starch (RS) content and properties of legume flour. The legume flours (mung bean, red kidney bean and soybean) were naturally fermented for 1 day and the fermented legume flours were debranched by hydrolyze the -1,6-Glycosidic Linkages by pullulanase (40 U/g) at 50 oC for 12 24 36 and 48 hours. The optimal incubation time with high degree of pullulanase hydrolysis was 24 hours. The fermented debranched flours were then induced at 4 oC for 1 3 5 7 and 14 days. The results showed that the optimum retrogradation time was 14 days with high RS content. The modified resistant starch was analyzed its granule structure by Scanning Electron Microscope (SEM) and showed that there was not found the granule starch with an irregular shape. The crystalline structure of the modified resistant starch by X-Ray diffractometer (XRD) showed that all 3 kinds of legumes were A-type patterns. It was found from this study that the process used to modify the starch can increase the RS content with the different granule structure and crystalline structure, resulting in a variety of resistant starch that could be applied as food ingredients in healthy foods.